(NbESY(B: [(NrOMAN(B]s (NgLAWA (B"(Nu tIHONA(B" /s (N~ASTX (B7s - (NdOSTOEWSKIJ(B, (NfEDORs ((NlENINGRAD(B:s (NnAUKA(B,s, 1990)
(Nw SEDXMOJ TOM sOBRANIQ SO^INENIJ WO[EL ROMAN (B"(NbESY(B".s
rus
Keywords: (NkLASSI^ESKAQ PROZAs; (NpSIHOLOGI^ESKIJ ROMANs; (NsATIRAs